Antimicrobial Resistance Pattern of Enterobacter Species Isolated from Different Clinical Specimens in a Tertiary Care Hospital of Bangladesh (Bangladesh Journal of Medical Microbiology, 2019)
The present study was undertaken to determine the antimicrobial resistance pattern of Enterobacter species to guide the clinician in selecting the best antimicrobial agent for an individual patient. A total of 50 clinical isolates of Enterobacter species were collected from different clinical specimens at the microbiology laboratory of BSMMU between August, 2018 and September, 2019. The two main species of Enterobacter, E.cloacae and E.aerogenes were identified by biochemical tests. Antimicrobial susceptibility testing was performed by Kirby Bauer disc diffusion method and reported according to CLSI guidelines. Majority (56%) of the isolated Enterobacter were E.cloacae, 40% were E.aerogenes and 4% were other species. The Enterobacter isolates showed relatively high resistance rates to the cephalosporins including cefoxitin (82%), cefixime (62%), ceftazidime (46%) and ceftriaxone (46%). Resistance to the carbapenems and aminoglycosides was relatively low. The high resistance rates of Enterobacter species to multiple antibiotics makes it necessary for antimicrobial susceptibility testing to be conducted prior to antibiotic prescription.Bangladesh J Med Microbiol 2019; 13 (2): 3-6